Evaluation of MicroScan rapid panels for detection of high-level aminoglycoside resistance in enterococci. - Woods, G L (1993)
The ability of MicroScan rapid panels to detect high-level aminoglycoside-resistant enterococci was evaluated. By agar dilution, 46 of 139 isolates were susceptible to gentamicin (GNT) and streptomycin (STRP); the rest were highly resistant to one or both agents. Rapid panels detected 97.5% of STRP- and GNT-resistant isolates and had a specificity of 95.6%. Detection of resistance by conventional panels at 18 h was 64.6% for STRP and 90.2% for GNT.